Fayyumic Glosses in Papyrus Chester Beatty VII - Bąk, Tomasz Bartłomiej (Orientalia, 2024)
Papyrus Chester Beatty VII is a unique witness to the Greek text of the Book of Isaiah, with brief marginal glosses in the Fayyumic dialect of the Coptic language. The article presents the manuscript collection followed by analyses of all the marginal annotations or glosses. The glosses are presented into several categories: i) illegible, ii) probable, iii) grammatical, and iv) legible words. These Fayyumic glosses provide evidence for the transition from the oral to the written tradition of the Coptic language.